Rare earth elements distribution in the river sediments of Ditrău Alkaline massif, Eastern Carpathians. - Valentin Nicolae Coțac; Ovidiu Gabriel Iancu; Nicușor Necula; Marius Cristian Sandu; Aurelia Andreea Loghin; Ovidiu Chișcan; George Stoian (PLoS ONE)
Ditrău Alkaline Massif is one of the few syenitic Massifs in Europe subjected to mining exploration in the past, located in the Eastern Carpathians, Romania. The heterogenous petrography includes acid to ultrabasic rocks such as syenites, hornblendites, and diorites, making it the defining feature of the Massif. In this study, we analyze the river bed sediments of two rivers, Ditrău and Jolotca, draining the Ditrău Alkaline Massif to determine their geochemical composition, with particular interest in Rare Earth Elements. The analysis was carried out with various analytical methods, including Inductive Coupled Plasma Mass Spectrometry, powder X-ray diffractometry, and electronic microscopy for mineralogical analysis to determine the presence of heavy minerals and quantify the concentration of Rare Earth Elements in the river sediment samples. The results indicate the existence of heavy minerals and Rare Earth Elements in bearing minerals such as Monazite and Epidote. High concentration values of Light Rare Earth Elements are identified, with values more than double compared to the Upper Continental Crust in some cases, of which stands out Cerium with 175.47 mg·kg-1 and Lanthanum with 108.32 mg·kg-1. Most samples share three main minerals: Quartz, K Feldspar, and Albite, while Diopside is only present in the Jolotca sediment samples, and Plagioclase exists in Ditrău samples. Moreover, many identified trace elements, such as Niobium, Tantalum, and Zirconium, indicate high enrichments, with samples' mean value of 265.62 mg·kg-1 for Zirconium and 200.24 mg·kg-1 for Niobium. The sum of Rare Earth Elements identified in the analyzed river sediments is 385.01 mg·kg-1 for Ditrău samples and 368.72 mg·kg-1 for Jolotca, with Cerium being the most significant element. The La/Th and Hf distinction plots suggest a mixed felsic/basic source for the Ditrău area and an acidic source for the Jolotca area.